Mathematical language at technical university - Dubinina, O.; Kornil, T. (НТУ "ХПІ", 2016)
Іn the article is analyzed philosophical and mathematical engineering aspect of intended use of mathematical language in higher technical education at the present stage of its development, based on the characteristics of the mathematical language in didactic space of technical university. Considered a problem of low skills in mathematical language of the students, and as a consequence – development of mathematical speech. Offered possible areas of improvement of mathematical language mastering by the students during professional training based on deepening application of functions of mathematical language (communication, idea forming, epistemological, integrating, nominative, information-preserving, culture bearing) in the educational process.

У статті проаналізовано філософський та інженерний аспект призначення математичної мови у вищій технічній освіті на сучасному етапі її розвитку, спираючись на особливості математичної мови у дидактичному просторі технічного університету. Розглянуто проблему недостатнього рівня володіння студентами математичною мовою, і, як наслідок, - розвитку математичного мовлення. Запропоновано можливі напрями удосконалення засвоєння математичної мови студентами у ході професійної підготовки на підґрунті цілеспрямованого поглиблення застосування функцій математичної мови (комунікаційної, мислеутворювальної, гносеологічної, інтегруючої, номінативної, інформаційно-зберігаючої, культуроносної) у навчальному процесі.
Математична мова в технічному університеті
Keywords: mathematical speech; mathematical language functions; professional training; математичне мовлення; функції математичної мови; математична культура інженера; студенти